2013
DOI: 10.1007/s10096-013-1881-1
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of Ferulago capillaris essential oil against Candida, Cryptococcus, Aspergillus and dermatophyte species

Abstract: This study evaluates the composition, antifungal activity and mechanism of action of the essential oil of Ferulago capillaris (Link ex Spreng.) Cout. and its main components, limonene and α-pinene, against clinically relevant yeasts and moulds. Essential oil from the plant's aerial parts was obtained by hydrodistillation and analysed by gas chromatography (GC) and gas chromatography/mass spectrometry (GC-MS). Essential oil showed high contents of limonene (30.9%) and α-pinene (35.8%). Minimum inhibitory concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 29 publications
3
38
0
3
Order By: Relevance
“…Furthermore, it has recently been suggested by Saville et al (2006) that this inhibitory activity alone can be used to treat infection in animal models of invasive candidiasis. The influence of the methanolic extract on its yeast -mycelium transition, at concentrations below the MIC, was already reported for some essential oils (Vale-Silva et al 2010;Zuzarte et al 2012;Pinto et al 2013). In this work, we provided evidences, for the first time, of the antifungal properties of the C. coccineum methanolic extract.…”
Section: Resultssupporting
confidence: 71%
“…Furthermore, it has recently been suggested by Saville et al (2006) that this inhibitory activity alone can be used to treat infection in animal models of invasive candidiasis. The influence of the methanolic extract on its yeast -mycelium transition, at concentrations below the MIC, was already reported for some essential oils (Vale-Silva et al 2010;Zuzarte et al 2012;Pinto et al 2013). In this work, we provided evidences, for the first time, of the antifungal properties of the C. coccineum methanolic extract.…”
Section: Resultssupporting
confidence: 71%
“…Some Ferulago species have been used in folk medicine for their sedative, tonic, digestive, anti-parasitic and aphrodisiac properties [13]. F. angulata has already shown to have high antioxidant properties [14].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with our results, Bernardes et al 8 observed a 95% reduction in germ cell formation when C. albicans cells (ATCC 10-231) were treated with raw glycolic 10% (v/v) extract from fresh Aloe vera leaves. Interestingly, Pinto et al 10 demonstrated an effect of the Ferulago capillaris essential oil on cells during inhibition of germ tube formation in C. albicans, which demonstrated that oxidative stress affects the enzymatic activity as well as cell mitochondrial membrane potential and results in growth inhibition and death. Given the high cost of the required methods, it was impossible to analyze the composition of the essential oil investigated in this study, particularly for the two primary active components, α-pinene and 1,8-cineole 11 .…”
mentioning
confidence: 99%